Effects of Bound and Free Phenols from Wheat Bran on Intestinal Flora Evaluated by in Vitro Simulated Gastrointestinal Digestion and Colonic Fermentation - HE Ying, ZHAO Wenhong, GUAN Erqi (Shipin Kexue)
In order to explore the effects of bound and free phenols from wheat bran on the gut microbiota during in vitro gastrointestinal digestion and colonic fermentation, this study conducted in vitro fermentation of bound and free phenols using fecal filtrates and evaluated changes in the antioxidant activity of the fermentation broth, the production of short-chain fatty acids (SCFAs) was determined by gas chromatography-mass spectrometry (GC-MS), and the changes in microbial community structure and abundance in fermentation broth were analyzed by 16S rRNA gene high-throughput sequencing. The results showed that compared with free phenols, the addition of bound phenols significantly improved the antioxidant activity of the fermentation broth and increased the production of SCFAs. The results of in vitro fecal fermentation showed that the addition of bound or free phenols reduced the relative abundance of the harmful bacterium Escherichia coli. Moreover, compared with free phenols, bound phenols significantly increased the relative abundance of beneficial bacteria (such as Bacteroides and Bifidobacterium). In summary, wheat bran bound phenols significantly improved the antioxidant capacity of the fermentation broth, promoted the production of SCFAs, and regulated the diversity of the gut microbiota, thereby being beneficial to human intestinal health.